Emotional expressivity as a moderator between self-esteem and prosocial behavior among undergraduate university students in Pakistan - Kausar, Asia; Alis, Norzaliza; Ismail, Suzila (Nurture, 2023)
Purpose: The current study focuses on how emotional expressivity influences the link between prosocial activities and self-esteem in undergraduate students. Design/Methodology/Approach: The study’s sample consisted of 528 college students, with ages ranging from 17 to 24 years. Of the participants, 52.8% identified as female and 47.2% identified as male. The participants in the study were provided with Rosenberg’s self-esteem scale, a measure of prosocial propensity, and an emotional expressivity scale. Statistical Package for Social Science was used to generate the results. Findings: The findings reveal the relationship between self-esteem and prosocial behavior, as well as the contribution of emotional expressivity as a modifier in that correlation. It was further explored that people who scored high on self-esteem and emotional expressivity were more likely to engage in prosocial behaviors. Conclusion: Gaining insight into the underlying factors that contribute to the correlation between self-esteem and prosocial behaviour is crucial to the advancement of strategies aimed at fostering and demonstrating prosocial behaviour. Research Limitation: One possible limitation of the study is its reliance on self-reported measures, which may be subject to bias regarding social desirability and may not completely capture individuals’ actual behaviours. To supplement self-reported data, future studies could use observational or experimental approaches. Practical Implication: The study’s conclusions have consequences for educators, counselors, and policymakers. Understanding the function of emotional expressivity in encouraging prosocial behavior can help guide initiatives aimed at creating a pleasant and supportive atmosphere in educational institutions and communities. Contribution to Literature: This study improves the existing body of facts by looking into the relationship between self-esteem, emotional expressivity, and prosocial behaviors. It enhances our understanding of the aspects that drive prosocial behavior and emphasizes the status of moderation for emotional expressivity in the context of this connection.